2011
DOI: 10.1155/2011/393521
|View full text |Cite
|
Sign up to set email alerts
|

Intra-tumoral Heterogeneity ofKRASandBRAFMutation Status in Patients with Advanced Colorectal Cancer (aCRC) and Cost-Effectiveness of Multiple Sample Testing

Abstract: Abstract. KRAS mutation status is established as a predictive biomarker of benefit from anti-EGFr therapies. Mutations are normally assessed using DNA extracted from one formalin-fixed, paraffin-embedded (FFPE) tumor block. We assessed heterogeneity of KRAS and BRAF mutation status intra-tumorally (multiple blocks from the same primary tumor). We also investigated the utility and efficiency of genotyping a 'DNA cocktail' prepared from multiple blocks.We studied 68 consenting patients in two randomized clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 17 publications
0
78
0
Order By: Relevance
“…Of the 572 patients in the randomized population, 394 were tested for KRAS status with bidirectional sequencing and 453 were tested with the therascreen KRAS kit. Intratumoral heterogeneity with respect to KRAS mutation status has been previously reported 24,25 and may have contributed to the discordance between the analyses. In addition, several other factors may have contributed to the observed differences between the results from the therascreen KRAS kit and bidirectional sequencing, including differences in available tumor tissue samples between the analyses and the relative sensitivities of the assays.…”
Section: Commentmentioning
confidence: 84%
“…Of the 572 patients in the randomized population, 394 were tested for KRAS status with bidirectional sequencing and 453 were tested with the therascreen KRAS kit. Intratumoral heterogeneity with respect to KRAS mutation status has been previously reported 24,25 and may have contributed to the discordance between the analyses. In addition, several other factors may have contributed to the observed differences between the results from the therascreen KRAS kit and bidirectional sequencing, including differences in available tumor tissue samples between the analyses and the relative sensitivities of the assays.…”
Section: Commentmentioning
confidence: 84%
“…By also taking into account intratumoural heterogeneity, 26 KRAS and BRAF mutations are well demonstrated mutually exclusive events in colorectal cancer. 27,28 Therefore, their coexistence, although very likely in different cellular subclones, might represent a peculiar feature of MUTYHassociated-polyposis carcinogenesis.…”
Section: M1mentioning
confidence: 99%
“…One report, analyzing 233 genes, indicated that there may be differences in as few as 3% of genes between primary and metastatic sites (10 (11,12). Although the number of cases surveyed was small, the frequency of acquired mutations identified was not negligible.…”
Section: Introductionmentioning
confidence: 99%